Lanthanum-substituted Cobalt Ferrite Established by the Co-precipitation Process: Annealing Temperature Adjustment of Structural, Magnetic, and Dye Removal Characteristics - Rahmawati, Ramadona; Musadewi, Adiana; Prasetya, Nurdiyantoro Putra; Suharno, Suharno; Budiawanti, Sri; Rahardjo, Dwi Teguh; Riyatun, Riyatun; Utari, Utari; Iriani, Yofentina; Nuryani, Nuryani; Purnama, Budi (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Co-precipitation process was used for the synthesis of lanthanum-substituted cobalt ferrite nanoparticles at several annealing temperatures (Ta), i.e., 200 °C, 300 °C, and 400 °C, for 5 h. XRD spectral depicted that the produced nanoparticles sample indicates a single phase of fcc inverse spinel conforming to ICDD No 22-1086. The crystallite size (D) calculation at the strongest peaks shows the increase in enhancing the Ta i.e., 18.99 nm, 19.90 nm, and 23.21 nm for 200 °C, 300 °C, and 400 °C, respectively. The FTIR results showed absorption band at the tetrahedral site, v1 ~575 cm−1 and the octahedral site, v2 ~474 cm−1. The absorption bands indicate that the lanthanum ions have successfully replaced the Fe3+ cations in the original cobalt ferrite structure. According to the hysteresis loop, the coercive field's (HC) magnitude falls from 700 Oe down to 550 Oe as Ta increases. This result is consistent with the anisotropy constant which decreased from 0.77×104 erg/cm3 to 0.56×104 erg/cm3. The obtained nanoparticles also showed superior performance (much larger than 95%) for dye removal of Congo red. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).